The FeBr3-Catalyzed Transfer Hydrogenation of Styrene Derivatives under Mild Reaction Conditions - Kail, Sascha; Hilt, Gerhard (Synlett, 2024)
The transfer hydrogenation of alkenes was realized by using a simple transition-metal compound (FeBr3) and 1,4-cyclohexadiene (1,4-CHD) as the hydrogen donor. The conversion of a number of di- and trisubstituted alkenes was investigated, and even a tetrasubstituted alkene was successfully converted. Compared with previously published work with the more expensive InBr3, the reaction times were considerably reduced and significantly milder reaction conditions could be applied. Interestingly, a transformation that was catalytic in 1,4-CHD, with molecular hydrogen as a stoichiometric reducing agent at 1 bar, was also accomplished.
Keywords: addition reaction; alkenes; iron catalysis; hydrogenation; transfer hydrogenation; cyclohexadiene